Adaptation of the caffrey cultural competence health services in nursing students in Lima, Peru - Rosario Eleana Cuadros Rios; Anahi Indira De La Calle Castro; Silvia Elizabeth De La Calle Robles; Israel Robert Pariajulca Fernández (Faculty of Nursing Universitas Padjadjaran, 2026)
Background: In the Peruvian context, cultural sensitivity and awareness among healthcare professionals are essential due to the country’s multicultural nature. To strengthen nursing education, reliable instruments are needed to assess perceived knowledge, self-awareness, and cultural competence. Purpose: The aim of this study was to adapt the Caffrey Cultural Competence in Healthcare Scale for nursing students at a private university in Lima. Methods: The sample consisted of 246 nursing students in the final academic terms. The adaptation process followed international guidelines for translation and back-translation, with expert committee review achieving 100% agreement on semantic and conceptual equivalence. Data were collected through an online survey and analyzed using descriptive statistics, confirmatory factor analysis, and internal reliability estimation with McDonald’s Omega coefficient. Results: Fit indices were optimal for both the five-factor model (Comparative Fit Index = .991; Tucker-Lewis Index = .990; Root Mean Square Error of Approximation = .021) and the unifactorial model (Comparative Fit Index = .992; Tucker-Lewis Index = .991; Root Mean Square Error of Approximation = .020), with evidence favoring the latter due to its greater parsimony. Reliability analysis showed excellent values for the total score and the Knowledge dimension, adequate values for Comfort/Proximity, moderate values for Comfort/Distance and Awareness, and lower consistency for the National Policies dimension. Conclusions: The scale demonstrates structural validity and adequate reliability for its application among nursing students in Lima, representing a relevant contribution to the evaluation of cultural competence in diverse educational contexts.